Regarding the political power of the declaration of February 16, 1918 - Česlovas Laurinavičius (Politologija)
In this article, the genesis and development of an independent Lithuania-state is being discussed not only on the basis of the traditional methods of historical science, but also in respect to both geopolitical and politological points of view. Such an attempt is not new. At his time, Stasys Šalkauskis tried to solve the problem of Lithuanian self-dependence in a similar way, as if he was seeking an extension in the volume of reflection. (The article by Stasys Šalkauskis titled "Lithuania's Geopolitical State and the Problem of the Lithuanian Culture" is meant here; it was published in "Židinys," spring issue, 1938). Heretofore, at that time the maximum retrospect reserve embraced and limited itself to 20 years. Nowadays, it seems reasonable to discuss the problem of the independent Lithuania-state, although, in a retrospect of 80 years.